2017
DOI: 10.1590/1678-77572015-0187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyaluronic acid on bleeding following third molar extraction

Abstract: Objective To explore the effects of hyaluronic acid (HA) on bleeding and associated outcomes after third molar extraction.Methods Forty patients who had undergone molar extraction were randomly divided into two groups; 0.8% (w/v) HA was applied to the HA group (n=20) whereas a control group (n=20) was not treated. Salivary and gingival tissue factor (TF) levels, bleeding time, maximum interincisal opening (MIO), pain scored on a visual analog scale (VAS), and the swelling extent were compared between the two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
(17 reference statements)
0
18
2
1
Order By: Relevance
“…According to Gocmen et al (Gocmen et al, 2017), total of forty patients was included and mean patient age was 24.8 years (18-35 years). 0.8% HA was applied on the edge of the extraction socket for the HA group and no intervention for control group.…”
Section: Resultsmentioning
confidence: 99%
“…According to Gocmen et al (Gocmen et al, 2017), total of forty patients was included and mean patient age was 24.8 years (18-35 years). 0.8% HA was applied on the edge of the extraction socket for the HA group and no intervention for control group.…”
Section: Resultsmentioning
confidence: 99%
“…After extraction of the wisdom tooth, complications such as pain, redness, swelling, and burning sensation always accompany though in varying degrees. Many studies have attempted to minimize these, and hyaluronic acid has been reported to have a positive effect on surgical wound healing as well as on intraoral wound healing and pain relief [ 9 , 10 ]. Nolan et al [ 7 ] said that HA can reduce pain in the wound through barrier formation.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the benefit included the formation of early granulation tissue and the inhibition of inflammation and postoperative pain. Gokhan et al [40] explored the influence of HA on hemostasis after third molar intervention by measuring the tissue fluid level and bleeding time as primary outcomes, and visual analog scale score pain measurement, maximum inter-incisal opening, and swelling as secondary outcomes. The single application of HA in gel form could be a reason for the results.…”
Section: Discussionmentioning
confidence: 99%
“…HA can be used as a drug delivery material by various routes of administration. Tables 1 and 2 provide the results of a literature survey of English articles of randomized controlled clinical trials published from 2014 to 2018 describing the applications of HA in dentistry and oral and maxillofacial surgery [1363738394041].…”
Section: Ha Mutagenicitymentioning
confidence: 99%